Penguatan Nilai Karakter Nasionalisme Dan Ketahanan Mental Dalam Perspektif Ips Melalui Film “Jenderal Soedirman” Terhadap Siswa Dari Keluarga Broken Home - Zianika Zalfa Mufidha; Durrrotun Nafisah; Kusnul Khotimah; Silvi Nur Afifah (Jurnal Sains, Teknik, Ekonomi, dan Pendidikan, 2026)
This study aims to determine the effectiveness of the film General Soedirman in improving the character values of nationalism and mental resilience of students, especially those from Broken Home families (parents divorced or families in disharmony). This study uses a qualitative approach with a case study methodology. Data were obtained through observation, in-depth interviews and documentation of students, social studies teachers, and guidance and counseling (BK) teachers of SMP Negeri 57 Surabaya. The research findings show that the film General Soedirman has a double effectiveness. First, this film successfully internalizes the character values of nationalism, such as patriotism, willingness to sacrifice, immortality, loyalty, solidarity, and unity. Second, this film is able to improve the mental resilience of Broken Home students based on Grotberg's three sources of resilience, namely "I HAVE", "I AM", and "I CAN". Theoretically this study also highlights the relationship between Thomas Lickona's character education theory (moral knowledge, moral emotions, and moral action) and Grotberg's theory of mental resilience. The film "General Soedirman" (General Soedirman) is worthy of consideration as a social studies educational medium and a guidance and counseling tool to help students from broken homes develop character and mental resilience.